The Distribution of Immobilized Platinum and Palladium Nanoparticles within Poly(2‐vinylpyridine) Brushes. Issue 17 (1st August 2014) - Al‐Hussein, Mahmoud; Koenig, Meike; Stamm, Manfred; Uhlmann, Petra
<x xml:space="preserve">Abstract</x> Novel catalytic surfaces can be prepared by in situ synthesis of metal nanoparticles (NPs) inside polymer brush systems. To gain more control over the properties of these nanocatalysts, it is important to quantify their distribution inside the polymer brush and understand their formation process better. Here, measurements of the distributions of Pt and Pd NPs within poly(2‐vinylpyridine) (P2VP) brushes are reported. The amount of surface accumulation and the extent of penetration of the two metal NPs into the brush layer are determined using X‐ray reflectivity measurements. Quantitative analysis of the data reveals a significant difference between the distributions of the two NP species. Pd NPs exhibit higher accumulation at the surface and larger penetration depth within the brush. This difference in behavior is attributed to the different adsorption mechanisms exhibited by the two metal ions. Whereas Pt ions adsorb to the polymer brush via ionic bonds, Pd ions form complex coordination bonds. The different distributions of the NPs within the polymer brush are related to the previously investigated catalytic activity of these systems. The reported unusually high specific activity of Pt hybrid brushes, as compared with Pd ones, can now be explained by buried Pd NPs that do not take part in the catalytic reaction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>